Characterization of the useful life and structural performance of a reinforced concrete bridge in the City of Correntes-PE (Research, Society and Development, 2021)
Even though we know that the construction industry is constantly evolving, due to the emergence of construction techniques and materials, we note that there are still challenges to be faced: pathological manifestations. These, in turn, compromise the performance and useful life of the elements. Its occurrences are mainly due to the reduction of deadlines, inadequate design solutions, improper use of materials, unskilled labor, lack of maintenance, lack of inspection, among other aspects. The evaluation of a structural element is based on the precedence of guaranteeing durability and quality to ensure the integrity of users. Therefore, this article analyzed structural elements of a reinforced concrete bridge located in the city of Correntes-PE. The main objective of the work was to characterize the main pathological manifestations affecting the structural elements of the bridge. The process of characterization of degrading agents was carried out through non-destructive tests, such as the carbonation front, as provided for in EN 14630 (DIN, 2007) and the evaluation of surface resistance, through the sclerometry test, according to NBR 7584 (ABNT, 2012). The results allowed to characterize the strength of the concrete and the degree of degradation. Points with incidence of carbonation and exposed reinforcement were identified, denoting the need for preventive and corrective intervention, in order to prolong the useful life and performance of the evaluated artwork.